Ta „poważna drobnostka”. Nowe wydanie Baśni Johanna Wolfganga Goethego - Ćwiklak, Kornelia (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
In this article, the author discusses and reviews the first Polish critical edition of Johann Wolfgang Goethe’s The Green Snake and the Beautiful Lily (2015). The literary text was preceded by two elaborate scientific descriptions which the author of this article refers to. The primary focus is on the extensive German tradition of interpreting The Green Snake and the Beautiful Lily (Das Märchen, 1795), because the main spur of its development is the difficulty or inability to obtain its unambiguous interpretation due to the high degree of symbolism and the esotericism of this literary work. Both critical texts feature the following interpretation grounds: historic-literary – emphasizing the role of the literary circle of the Weimar Goethe and Schiller; historical – stressing the importance of the events associated with the French Revolution and its impact on the situation in Germany; philosophical – represented by Rudolf Steiner and his anthroposophic reading of this work; and poetological – focusing on the properties and functions of its poetics. Among the existing explication there is a lack of genology of the fairy tales and a lack of the placing the work in a broader context of ideas and works of Goethe, which, if taken into account could help to clarify its meanings.